Influences of rapid pacing-induced electrical remodeling on pharmacological manipulation of the atrial refractoriness in rabbits - Toshiki Chiba; Naoto Kondo; Akira Takahara (Elsevier, 2016)
Electrical remodeling plays a pivotal role in maintaining the reentry during atrial fibrillation. In this study, we assessed influence of electrical remodeling on pharmacological manipulation of the atrial refractoriness in rabbits. We used an atrial electrical remodeling model of the rabbit, subjected to rapid atrial pacing (RAP; 600 beats/min) for 2-4 weeks, leading to shortening of atrial effective refractory period (AERP). Intravenous administration of dl-sotalol (6 mg/kg), bepridil (1 mg/kg), amiodarone (10 mg/kg) or vernakalant (3 mg/kg) significantly prolonged the AERP both in the control and RAP rabbits. The extents in the RAP rabbits were similar to those in the control animals. On the other hand, prolonging effects of intravenously administered ranolazine (10 mg/kg) or tertiapin-Q (0.03 mg/kg) on the AERP in the RAP rabbits were more potent than those in the control animals. These results suggest that rapid pacing-induced electrical remodeling effectively modified the prolonging effects of ranolazine and tertiapin-Q on the AERP in contrast to those of clinically available antiarrhythmic drugs, dl-sotalol, bepridil amiodarone and vernakalant.